New insights on femoral head trabecular bone directionality in elderly humans using a micro-CT-based analysis - Amit Hadad; Yaron Bar-Ziv; Hila May (Scientific Reports)
Abstract The trabeculae of the femoral head are organized in response to mechanical forces acting on the bone, becoming increasingly anisotropic with age. This may elevate fracture risk under non-primary loading conditions, such as falls. However, normal trabecular angles and directional patterns have not been fully characterized. This study examined trabecular directionality in 62 proximal femora of 38 cadavers (mean age: 87.2 ± 8.2 years, range: 65–102) using micro-CT scans. Trabecular bone direction and dispersion were measured in coronal slices along the anteroposterior axis. Differences based on side and sex were examined, as well as associations with age and neck-shaft angle. We found that direction and dispersion are side and sex independent, with no significant correlation to age. However, trabecular bone direction in the midcoronal slice, as well as the multi-slice average, showed a significant negative correlation with the neck-shaft angle (r=-0.496 and r=-0.562, respectively, p < 0.001). Furthermore, the multi-slice average demonstrated significantly lower direction and higher dispersion values than those in the single-slice analyses. Nevertheless, the two measurement types were strongly correlated. Moreover, each individual had a unique trabecular pattern, although it followed a common structural blueprint. These findings enhance our understanding of femoral head biomechanics, with implications for orthopedic surgery, implant design, and forensic medicine.